Serotonin-modulating therapies for the management of chronic wounds - Budhiraja, Anuj; Mehta, Alisha; Ghebrehiwet-Kuflom, Johanna; Patel, Janmesh D.; How-Volkman, Christiane; Ali, Lara; Dahle, Sara; Isseroff, Roslyn Rivkah (Frontiers in Pharmacology, 2025)
IntroductionChronic wounds are a significant source of patient morbidity, and ineffective treatment can lead to complications that are difficult and costly to manage. Given the limitations of current therapies, repurposing medications with well-studied safety and accessibility profiles offers a promising strategy for advancing wound care.MethodsA comprehensive review of the existing literature was conducted to evaluate the role of serotonin-modulating pharmacotherapy in wound healing.ResultsSerotonergic signaling plays a multifaceted role in wound healing and evidence increasingly supports serotonin-modulating pharmacotherapy as having favorable angio-regulatory, immunomodulatory, and antimicrobial wound healing effects. Preclinical and clinical studies have demonstrated that topical administration of serotonin-modulating pharmacotherapy may improve wound healing outcomes.Discussionfindings of this study provide support for the use of serotonin-modulating pharmacotherapy, with a special focus on topical application, as an adjunctive treatment for chronic, non-healing wounds and highlight the need for further translational clinical investigation.